Antioxidant and Anti-Inflammatory Effects of Opuntia Extracts on a Model of Diet-Induced Steatosis - Irene Besné-Eseverri; María Ángeles Martín; Gloria Lobo; M. Pilar Cano; María P. Portillo; Jenifer Trepiana (MDPI AG, 2024)
Oxidative stress and inflammation are widely recognised as factors that can initiate and facilitate the development of MAFLD. The aim of this study is to analyse the effect of low and high doses of Opuntia stricta var. dillenii peel extract (L-OD and H-OD, respectively) and Opuntia ficus-indica var. colorada pulp extract (L-OFI and H-OFI, respectively), which are rich in betalains and phenolic compounds, on oxidative stress, inflammation, DNA damage and apoptosis in rat livers with diet-induced steatosis. Steatotic diet led to increased final body and liver weight, serum transaminases, hepatic TG content, oxidative status and cell death. H-OFI treatment decreased serum AST levels, while L-OFI reduced hepatic TG accumulation. Oxidative stress was partially prevented with H-OD and H-OFI supplementation, and pro-inflammatory cytokines levels were especially improved with H-OFI treatment. Moreover, H-OFI appears to prevent DNA damage markers. Finally, H-OD and L-OFI supplementation down-regulated the apoptotic pathway. In conclusion, both H-OD and H-OFI supplementation were effective in regulating the progression to metabolic steatohepatitis, triggering different mechanisms of action.